2011
DOI: 10.1016/j.ajpath.2011.07.024
|View full text |Cite
|
Sign up to set email alerts
|

Protease Activated Receptor-2 Mediates Activated Protein C–Induced Cutaneous Wound Healing via Inhibition of p38

Abstract: Activated protein C (APC) is a natural anticoagulant that exerts anti-inflammatory and cytoprotective properties mediated through the protease activated receptor (PAR)-1. APC can also proteolytically cleave PAR-2, although subsequent function is unknown. On the basis of recent evidence that APC promotes wound healing, the aim of this study was to determine whether APC acts through PARs to heal murine excisional wounds or to regulate human cultured keratinocyte function and to determine the signaling mechanisms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
70
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(73 citation statements)
references
References 53 publications
3
70
0
Order By: Relevance
“…Nonetheless, numerous studies have shown that APC exerts antiinflammatory and cyto-protective properties in various organs and that these effects are often mediated by endothelial protein C receptor (EPCR) and proteinase-activated receptors (PARs) (14)(15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, numerous studies have shown that APC exerts antiinflammatory and cyto-protective properties in various organs and that these effects are often mediated by endothelial protein C receptor (EPCR) and proteinase-activated receptors (PARs) (14)(15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%
“…35,52 In contrast, activated protein Cemediated activation of PAR-2 inhibited the phosphorylation of p38 in human primary keratinocytes. 53 Therefore, p38 signaling, modulated by PAR-2 activation, may be highly dependent on the cellular context or type.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study showed that under hypoxic conditions, p38 mitogen-activated protein kinase (p38MPAK) is essential for fibroblast proliferation and acts as a modulator of pro-inflammatory responses in rheumatological conditions (Mortimer et al 2007). Indeed, if protease-activated receptors (PARs) are activated, they signal via p38 to induce immune responses (Julovi et al 2011;Riewald & Ruf 2005). Thus, we expected that activation of p38 by APC under hypoxic conditions would be involved in the proliferation and anti-inflammatory response of RAFb.…”
Section: Discussionmentioning
confidence: 99%
“…Cell proliferation assays were performed as described previously (Julovi et al 2011). Cells (2 × 10 3 cells/well) were seeded into 96-well microplates to a final volume of 200 μL and incubated for 4 h to allow cells to attach.…”
Section: Cell Proliferation Assaysmentioning
confidence: 99%
See 1 more Smart Citation